Exploring teachers’ and learners’ overlapped turns in the language classroom: Implications for classroom interactional competence - Cancino Avila, Marco Octavio (Studies in Second Language Learning and Teaching, 2019)
The language choices that teachers make in the language classroom have been found to influence the opportunities for learning given to learners (Seedhouse, 2004; Walsh, 2012; Waring, 2009, 2011). The present study expands on research addressing learner-initiated contributions (Garton, 2012; Jacknick, 2011; Waring, Reddington, & Tadic, 2016; Yataganbaba & Yıldırım, 2016) by demonstrating that opportunities for participation and learning can be promoted when teachers allow learners to expand and finish their overlapped turns. Audio recordings of lessons portraying language classroom interaction from three teachers in an adult foreign language classroom (EFL) setting were analyzed and discussed through conversation analysis (CA) methodology. Findings suggest that when teachers are able to navigate overlapping talk in such a way that provides interactional space for learners to complete their contributions, they demonstrate classroom interactional competence (Sert, 2015; Walsh, 2006). The present study contributes to the literature by addressing interactional features that increase interactional space, and an approach to teacher and learner talk that highlights CA’s methodological advantages in capturing the interactional nuances of classroom discourse.